KESANTUNAN TINDAK TUTUR EKSPRESIF GURU BAHASA INDONESIA PADA KELAS VII.1 SMP NEGERI 34 PADANG - Adha, Rahmatul; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTThe problem studied was the teacher's expressive speech act and the politeness principle used by the Indonesian language teacher in class VII 1 Padang 34 Middle School. In this study, the types of expressive speech acts and language politeness principles were described which were used by Indonesian language teachers in class VII 1 of Padang State Middle School 34. Data collection is done by referring to the method. The method of referencing is listening to the use of language to obtain lingual data. The techniques used in this study are (1) recording technique, is a listening activity using a recording device, (2) recording technique, is the activity of recording data that has been recorded. Based on the data analysis conducted it can be concluded as follows. First, the results of this study indicate that Indonesian language teachers in class VII 1 of SMP Negeri 34 Padang used six types of expressive speech acts, namely expressive speech criticizing, expressive speech acts praising, expressive speech acts blaming, expressive speech acts thanking, speech acts expressive condolences, and expressive speech acts apologize. The most dominant speech act found is expressive speech criticism and the least is expressive speech act apologizing. Secondly, the politeness principle of Indonesian language teachers in class VII 1 of SMP Negeri 34 Padang uses the maxim of generosity, maxim of wisdom, maxim of appreciation, maxim of consensus, maxim of simplicity, and maxim of conclusions. The most dominant method used by Indonesian teachers in class VII 1 is the maxim of generosity and the most used is the maxim of conclusions. Kata Kunci: Kesantunan, Tindak Tutur Ekspresif